Rocuronium pharmacokinetics and pharmacodynamics in the adductor pollicis and masseter muscles. Issue 6 (22nd February 2016) - Vega, E. A.; Ibacache, M. E.; Anderson, B. J.; Holford, N. H. G.; Nazar, C. E.; Solari, S.; Allende, F. A.; Cortínez, L. I.
Abstract : Background: The aim of this study was to characterize the dose–effect relationship of rocuronium at the adductor pollicis and masseter muscles. Methods: Ten, ASA I, adult patients, received a bolus dose of rocuronium 0.3 mg/kg during propofol based anesthesia. Train‐of‐four (TOF) was simultaneously monitored at the masseter and the adductor pollicis muscles until recovery. Rocuronium arterial serum concentrations were measured during 120 min. The first twitch of the TOF response was used to characterize the time–effect profile of both muscles using pharmacokinetic–pharmacodynamic analysis in NONMEM. A decrease in NONMEM objective function (∆OFV) of 3.84 points for an added parameter was considered significant at the 0.05 level. Results: Onset time at the masseter (mean ± SD, 1.5 ± 0.9 min) was faster than at the adductor pollicis (2.7 ± 1.4 min, P < 0.05). Recovery, measured as the time to TOF ratio = 0.9 was similar between muscles 29.9 ± 6.7 (adductor pollicis) vs. 29.3 ± 8.1 (masseter). ( P = 0.77). The estimated pharmacodynamic parameters [mean (95% CI)] of the adductor pollicis muscle and the masseter muscle were; plasma effect‐site equilibration half‐time (teq) 3.25 (2.34, 3.69) min vs. 2.86 (1.83, 3.29) min, (∆OFV 383.665); Ce50 of 1.24 (1.13, 1.56) mg/l vs. 1.19 (1.00, 1.21) mg/l, (∆OFV 184.284); Hill coefficient of 3.97 (3.82, 5.62) vs. 4.68 (3.83, 5.71), (∆OFV 78.906). Conclusions: We found that the masseter muscle has faster onset of blockade and similar recovery profile than adductor pollicis muscle. These findings were best, explained by a faster plasma effect‐site equilibration of the masseter muscle to rocuronium.